Assessing urban mass sports health development strategies using generalized orthopair fuzzy decision making under healthy china vision - Mengchu Li; Bo Zhang (Scientific Reports, 2026)
Abstract The urban mass sports are highly important in encouraging the population to live fruitfully and healthy lives, as outlined in the vision of a healthy China. But, there is yet a lack of holistic decision-making frameworks which are able to deal with uncertainty and expert hesitation in assessing urban mass sport health development strategies. This paper presents a q-rung orthopair fuzzy Faire Un Choix Adequat (qROF-FUCA) algorithm to assess and rank the strategies of developing urban mass sports health in the case of uncertainty and reluctance of experts to conduct their estimation. The evaluation of fifteen alternative strategies is performed on the basis of nine metrics, including accessibility, participation, quality of infrastructure, policy support, technological innovation, cost, and the impact on the environment. The evaluation data were gathered through the lens of four domain experts—who were knowledgeable in urban sports planning, public health, infrastructure development, and community sports management, respectively. The validation and normalization of the expert judgments in the qROF framework were done in a consistency-based method for making the judgments reliable and consistent. According to the results, nighttime urban fitness areas, school-community participatory programs, and intelligent sports platforms can be considered the most efficient models to improve the level of population engagement and health results. The sensitivity analysis used in these rankings guarantees the strength of the rankings, while the novelty of the proposed methodology over the existing qROF-MCDM approaches and its superiority with respect to uncertainty handling ability over current approaches establish its robustness and ability to handle uncertainty. Moreover, consistency checks and sensitivity analysis are performed to test the robustness of the proposed framework and verify the stability and reliability of the results obtained by changing the values of the parameters. The results offer usable advice to policymakers and urban planners, as they offer a clear, transparent, and efficient structure to assist in strategic decision-making in urban sports health development.